Resistência de cultivares e seletividade de pesticidas como estratégias de manejo de ácaros-praga em citros - Silva, Rafael Rocha da (2013)
Citrus are attacked by pest mites such as the citrus rust mite Phyllocoptruta oleivora (Ashmead) (Acari: Eriophyidae), the Texas citrus mite Eutetranychus banksi and other tetranychid species of that cause serious damage to production. Strategies like the use of citrus genotypes with genetic characteristics that may influence pest populations and the application of products compatible with natural enemies could help in mite pests control. We aimed to evaluate the susceptibility of citrus scion and rootstocks to pest mites and rank pesticides according to their selectivity to a key predatory mite in order to develop ecological management strategies for pest mite control in citrus orchards. Adults of P. oleivora and Tetranychus sp. (Acari: Tetranychidae) were counted monthly from June 2011 to February 2013 in orange trees ‘Pera’ D6 and Valencia 'Tuxpan' grafted on 10 and 12 rootstock cultivars, respectively. Adults of P. oleivora, Eutetranychus banksi and Tetranychus sp. were counted monthly in every citrus scion grafted on ‘rangpur’ lime from April 2011 to February 2013 to assess the level of resistance. In addition, laboratory studies were conducted to determine the compatibility of pesticides with the generalist predatory mite Amblyseius largoensis Muma (Acari: Phytoseiidae), a key natural enemy of pest mites. The rootstock cultivars influenced the populations of pest mites in that the orange trees ‘Pêra’ D6 grafted on LVK x LCR 10 were more susceptible to the attack of P. oleivora compared to the rootstocks citrumelo ‘Swingle’ and TSKC x CTTR 002. Valencia orange 'Tuxpan' grafted on citrandarim 'Indian' was more susceptible to mite Tetranychus sp. when compared to HTR-051. The scion varieties influenced E. banksi and Tetranychus sp. so that the population peak of E. banksi was recorded in valencia 'Montemorellos’ in February 2012. Largest populations of Tetranychus sp. were observed in orange ‘lime’ compared to lemon tahiti IAC 5 and IAC 5-1 in January 2013. The scion varieties did not affect the population of P. oleivora. In some periods of the year the abundances of the mites P. oleivora and Tetranychus sp. were influenced by scion varieties grafted on different rootstocks suggesting in both cases, seasonality in the susceptibility of some citrus genotypes to these pests. Additionally, toxicity experiments revealed that neem and mineral oils as well as mancozeb are compatible with the predatory mite A. largoensis. The use of scion and rootstocks cultivars less susceptible to pests combined with the use of pesticides compatible with natural enemies may help in the control of citrus pests mites.